Industry 4.0 for SMEs 2020
DOI: 10.1007/978-3-030-25425-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Laboratory Case Study for Intuitive Collaboration Between Man and Machine in SME Assembly

Abstract: 335 12.1 Introduction "Industry 4.0" is the name given to the ongoing fourth industrial revolution, which is actually transforming worldwide factories. This concept was initially introduced by a German government strategic initiative in 2011 (Kagermann et al. 2013) and represents the current 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The experimental study of this work was developed in the laboratory scenario shown in Figure 1. A laboratory scenario has great adaptability for the identification of humanrobot solutions, development of new methodologies, application of algorithms and evaluation of collaborative human-robot workstations [21].…”
Section: Human-robot Collaborative Workpacementioning
confidence: 99%
“…The experimental study of this work was developed in the laboratory scenario shown in Figure 1. A laboratory scenario has great adaptability for the identification of humanrobot solutions, development of new methodologies, application of algorithms and evaluation of collaborative human-robot workstations [21].…”
Section: Human-robot Collaborative Workpacementioning
confidence: 99%
“…Future research should focus on the possibility to autonomously and dynamically adapt the workstation elements according to operators' psychophysical work conditions, needs, and wants [32]. This will surely improve both physical and cognitive ergonomics and therefore have a good impact on productivity.…”
mentioning
confidence: 99%
“…The product or process quality evaluation aims to investigate if a task or an activity requires improvements in terms of standardization and reduction of process instability or variability [35,36]. From a manufacturing approach, variability is defined as an inherent process deviation from a nominal value.…”
Section: Metrics For Product/process Quality Evaluation: Variabilitymentioning
confidence: 99%
“…From a manufacturing approach, variability is defined as an inherent process deviation from a nominal value. In [35], process variability is identified as a coefficient of variation CV,…”
Section: Metrics For Product/process Quality Evaluation: Variabilitymentioning
confidence: 99%